Do we really ponder about necessity of intravenous hydration in acute bronchiolitis? - Yıldırım, Şule (Colomb Med (Cali), 2016)
OBJECTIVE: The goal was to establish the role of intravenous hydration therapy on mild bronchiolitis. METHODS: This was a retrospective case control study. Infants between 1 month and 2 years of age admitted to our general pediatrics ward between June 2012 and June 2013 with a diagnosis of uncomplicated acute bronchiolitis were enrolled to the study. Hospital medical files were reviewed to get information about children personal history, symptoms of the disease, disease severity scores and their management. Patients were classified into 4 groups according to the management; nebulized short-acting β(2)-agonist (salbutamol) +hydration; nebulized short-acting β(2)-agonist (salbutamol); hydration and neither bronchodilator nor hydration. We examined length of stay in the hospital as an outcome measure. RESULTS: A total of 94 infants were studied. There was no significant difference between groups in terms of length of stay in hospital. CONCLUSIONS: IV hydration is not effective on length of stay in hospital in mild acute bronchiolitis patients.